2020
DOI: 10.1021/acs.est.0c01914
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on Priming in Euphotic Sediments: Nutrient Enrichment Stimulates Export of Stored Organic Matter

Abstract: Estuarine sediments are important sites for the interception, processing, and retention of organic matter, prior to its export to the coastal oceans. Stimulated microbial cometabolism (priming) potentially increases export of refractory organic matter through increased production of hydrolytic enzymes. Using the microphytobenthos community to directly introduce a pulse of labile carbon into sediment, we traced a priming effect and assessed the decomposition and export of preexisting organic matter. We show enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Analysis of three explicitly photochemical molecular pools (probability > 0.95) indicated that explicitly photolabile MFs exhibited higher aromatic and humifaction degree (Figure ), which is consistent with previous irradiation-based studies, ,, also suggesting that the partially oxidized processes are probably predominant in estuarine ecosystems. Moreover, the photolabile pool had the highest CHOS% among the three pools (Figure and Figure ), supporting its facile photochemical degradation as reported from the deep sea, , porewater, and acid mine drainage, with the potential products of climate-impacting gases carbonyl sulfide, dimethyl sulfide, or methanesulfonic acid. Significant amounts of N-containing compounds produced after photoirradiation were also found in samples from both natural and anthropogenic sources and were interpreted by the photoinduced incorporation of dissolved organic nitrogen into DOM. , The photoresistant pool was dominated by the HU group (Figure ) that is also known to be biologically recalcitrant to heterotrophic microbes .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Analysis of three explicitly photochemical molecular pools (probability > 0.95) indicated that explicitly photolabile MFs exhibited higher aromatic and humifaction degree (Figure ), which is consistent with previous irradiation-based studies, ,, also suggesting that the partially oxidized processes are probably predominant in estuarine ecosystems. Moreover, the photolabile pool had the highest CHOS% among the three pools (Figure and Figure ), supporting its facile photochemical degradation as reported from the deep sea, , porewater, and acid mine drainage, with the potential products of climate-impacting gases carbonyl sulfide, dimethyl sulfide, or methanesulfonic acid. Significant amounts of N-containing compounds produced after photoirradiation were also found in samples from both natural and anthropogenic sources and were interpreted by the photoinduced incorporation of dissolved organic nitrogen into DOM. , The photoresistant pool was dominated by the HU group (Figure ) that is also known to be biologically recalcitrant to heterotrophic microbes .…”
Section: Resultssupporting
confidence: 72%
“…To study the potential photochemical reactivity of samples without employing irradiation experiments, a favorable practice is to compare the MFs occurring in samples from various aquatic ecosystems with the classified MFs acquired from previously performed irradiation experiments. Despite the success of this “molecular matching” approach in evaluating the photochemical quality of the samples, many concerns remain. First, considering the complexity of the DOM transformation, the relationship between the classes of photochemistry related MFs and their chemical composition is complicated and probably nonlinear, which cannot be simply elucidated through the molecular matching approach.…”
Section: Introductionmentioning
confidence: 99%
“…These nutritional parameters contributed strongly to the determination of DOM composition. Nutrient enrichment may increase the degradation of previously unavailable DOM by increasing the production of hydrolytic enzymes from stimulated microbial cometabolism . Eutrophication promotes the transformation of tyrosine-like components to protein-like components with elevated humification and molecular weight .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the transfer of high‐quality OC from the surface to deeper layers may prime microbial communities and in this way stimulate degradation of more refractory OC found in deeper sediment layers (Middelburg, 2018 ; van Nugteren et al, 2009 ). This can lead to significantly increased total OC remineralization rates, although the process is known to vary between environmental settings (Bengtsson et al, 2018 ; Riekenberg et al, 2020 ; van Nugteren et al, 2009 ).…”
Section: Links Between Seabed Sediment Oc and Mobile Demersal Fishingmentioning
confidence: 99%